The regulatable MAL32 promoter in Saccharomyces cerevisiae: characteristics and tools to facilitate its use - Meurer, Matthias; Chevyreva, Veronika; Knop, Michael (Yeast, 2017)
Here we describe a set of tools to facilitate the use of maltose and the MAL32 promoter for regulated gene expression in yeast, alone or in combination with the GAL1 promoter. Using fluorescent protein reporters we find that under non-inducing conditions the MAL32 promoter exhibits a low basal level of expression, similar to the GAL1 promoter, and that both promoters can be induced independently of each other using the respective sugars, maltose and galactose. While their repression upon glucose addition is immediate and complete, we found that the MAL32 and GAL1 promoters each exhibit distinct induction kinetics. A set of plasmids is available to facilitate the application of the MAL32 promoter for chromosomal modifications using PCR targetting and for plasmid based gene expression. Copyright © 2016 John Wiley & Sons, Ltd.
First published: 23 November 2016
Gesehen am 04.08.2017